2001
DOI: 10.1080/02699930143000013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of environmental problems: A coherence model of cognition and emotion

Abstract: This article presents a computational framework for understanding how media information about environmental problems influences cognition, emotion, and behaviour. The theoretical assumptions are formally specified and implemented in the computer model ITERA (Intuitive Thinking in Environmental Risk Appraisal) using a constraint satisfaction network.The model makes predictions about the cognitive evaluation of environmental problems, about the development of distinct emotions (anger and sadness), and about the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 61 publications
2
39
1
Order By: Relevance
“…In addition, research on appraisal theories of emotions has clearly shown that different emotions correspond with different patterns of appraising a situation (Nerb and Spada 2001;Ortony, Clore, and Collins 1988;Reisenzein and Hofmann 1993; for an overview, see Scherer 1999). Appraisal theories define appraisal as the cognitive evaluation of a situation with respect to the demands, constraints, and resources in the situation on the one hand, and the goals and resources of the individual on the other.…”
Section: Environmental Education Researchmentioning
confidence: 98%
See 4 more Smart Citations
“…In addition, research on appraisal theories of emotions has clearly shown that different emotions correspond with different patterns of appraising a situation (Nerb and Spada 2001;Ortony, Clore, and Collins 1988;Reisenzein and Hofmann 1993; for an overview, see Scherer 1999). Appraisal theories define appraisal as the cognitive evaluation of a situation with respect to the demands, constraints, and resources in the situation on the one hand, and the goals and resources of the individual on the other.…”
Section: Environmental Education Researchmentioning
confidence: 98%
“…If responsibility for a negative outcome is attributed to human causes, anger is typically the main emotion (Keltner, Ellsworth, and Edwards 1993). By manipulating media reports on environmental accidents involving supertankers, Nerb and Spada (2001) found that emphasizing human causes elicited more anger than emphasizing natural causes. Additionally, guilt may be elicited when people consider themselves responsible for negative consequences (Weiner 1995).…”
Section: Environmental Education Researchmentioning
confidence: 99%
See 3 more Smart Citations